Contribution of User-Generated Content to Support the Promotion of Pura Mangkunegaran on Digital Platforms - Nur Laili Mardhiyani; Arifa Rachma Febriyani; Mirtha Raihany; Nur Laili Noviyani; Ahmad Muntakhib (Diponegoro University, 2025)
This article explains how the role of social media users is part of the development of Pura Mangkunegaran tourism in the form of support through digital platforms. The research method used is descriptive quantitative which includes stages of data collection, data analysis, and data interpretation. Data was taken from respondents who had engagement with Pura Mangkunegaran content which was linked to sentiment analysis and social networks using social media analysis tools based on certain keywords related to Mangkunegaran. The research results show that User Generated Content (UGC) has an important role in supporting Pura Mangkunegaran tourism promotion. Influencers play an important role in spreading Pura Mangkunegaran content, so that content is not only intended for followers, but also for everyone. The more content is created and distributed, the more visible the contribution of UGC will be. Positive sentiment dominates the discussion context on social networks and negative sentiment keywords that appear are not related to tourism.